2020
DOI: 10.1021/acs.est.0c01073
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of Monoethylhexyl Phthalate in Lipid Accumulation via Inhibiting Fatty Acid Beta-Oxidation on Hepatic Cells

Abstract: Monoethylhexyl phthalate (MEHP) is one of the main active metabolites of the plasticizer di(2-ethylhexyl) phthalate. It has been known that MEHP has an impact on lipolysis; however, its mechanism on the cellular lipid metabolism remains largely unclear. Here, we first utilized global lipid profiling to fully characterize the lipid synthesis and degradation pathways upon MEHP treatment on hepatic cells. Meanwhile, we further identified the possible MEHP-targeted proteins in living cells using the cellular therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…15140122, Gibco, USA) at 37 °C in a humidified atmosphere with 5% CO 2 . Considering that HepG2 can exert the normal hepatocyte-specific functions, such as lipoprotein transport, cholesterol and triglyceride metabolism, and so on, and it has been characterized as a metabolically relevant model feasible for omics and toxicological studies, this cell line was consequently used as the in vitro assay for 3-BHA-induced lipid accumulation herein.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…15140122, Gibco, USA) at 37 °C in a humidified atmosphere with 5% CO 2 . Considering that HepG2 can exert the normal hepatocyte-specific functions, such as lipoprotein transport, cholesterol and triglyceride metabolism, and so on, and it has been characterized as a metabolically relevant model feasible for omics and toxicological studies, this cell line was consequently used as the in vitro assay for 3-BHA-induced lipid accumulation herein.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Lung tissue or serum metabolite (Ivanisevic et al, 2013) and lipid (Chen et al, 2013;Xu et al, 2020) extraction methods were obtained from prior studies. For the lung tissue samples, weighted ($10 mg) freeze-tissue samples were homogenized using steel beads with thaw twice.…”
Section: Metabolite and Lipid Extractionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC, US) has reported that MEHP is widely detected in human urine with concentrations ranging from 14.1 to 39.7 μg/L in the US population . There is strong evidence suggesting that MEHP possesses endocrine-disrupting and obesogenic effects on human health, disturbs the energy balance due to its activation effect on peroxisome proliferator-activated receptor γ (PPAR-γ), , and inhibits fatty acid oxidation, according to our recent study . Although MEHP affects different physiological functions, its toxic mechanisms and roles in the cellular system remain largely elusive.…”
Section: Introductionmentioning
confidence: 94%
“…22 There is strong evidence suggesting that MEHP possesses endocrine-disrupting and obesogenic effects on human health, disturbs the energy balance due to its activation effect on peroxisome proliferator-activated receptor γ (PPAR-γ), 23,24 and inhibits fatty acid oxidation, according to our recent study. 25 Although MEHP affects different physiological functions, its toxic mechanisms and roles in the cellular system remain largely elusive. The various adverse effects caused by MEHP, therefore, is likely attributed to its multiple protein targets contributing to the toxicity.…”
Section: ■ Introductionmentioning
confidence: 99%